THE IMPACT OF LAVENDER AROMATHERAPY ON PAIN INTENSITY AND BETA-ENDORPHIN LEVELS IN POST-CAESAREAN MOTHERS - Yohana Putri Apryanti; Suhartono Suhartono; Ngadiyono Ngadiyono (Belitung Nursing Journal, 2017)
Background: Caesarean section is one of the most common interventions to overcome labor complications. However, pain cannot be avoided after the surgery. Lavender aromatherapy is considered as one of non-pharmacological therapy to reduce pain and increase beta-endorphin levels. Objective: To examine the effect of lavender aromatherapy on the intensity of pain and beta-endorphin levels in post-caesarean mothers. Methods: This was a quasi-experimental study with pretest and posttest with control group at Sembiring Delitua General Hospital in Indonesia on December 2016 to February 2017. There were 40 samples selected using purposive sampling, with 20 samples assigned in the experiment and control group. Numerical Rating Scale (NRS) was used to measure pain and ELIZA methods to measure beta-endorphin levels. Independent t-test and paired t-test were used for data analysis Results: Results of this study showed that there was a significant difference in the mean value of pain intensity levels (p = 0.000) and beta-endorphin levels (p = 0.023) between experiment and control group. Conclusion: There was a significant effect of lavender aromatherapy on the decrease of pain intensity and the increase of beta-endorphin hormone in post-caesarean mothers. It is expected that lavender aromatherapy can be used as an alternative treatment to reduce pain and increase beta-endorphin levels in post-caesarean mothers.